The Effect of Deployment on Pulmonary Function in Military Personnel With Asthma. Issue 1 (4th January 2022) - Woods, Jeffrey T; Walter, Robert J; Houle, Mateo C; Barber, Brian S; Morris, Michael J
ABSTRACT: Introduction: Military personnel with a diagnosis of asthma report increased respiratory symptoms in the deployment and post-deployment periods. The long-term effect of deployment on pulmonary function in this population is unknown. This study sought to determine the effect of deployment on post-deployment pulmonary function in active duty military personnel with asthma. Materials and Methods: A retrospective chart review of active duty military personnel with deployment to southwest Asia and an ICD-9 diagnosis of asthma with documented pre- and post-deployment spirometry was performed. Results: A total of 642 active duty individuals with a diagnosis of asthma and documented spirometry with deployment to southwest Asia between 2006 and 2015 were identified. Of these, 76 individuals were identified with pre- and post-deployment spirometry. There was no significant change in the post-deployment forced expiratory volume at 1 second (% predicted), from 86.0 ± 14.8 to 87.6 ± 14.4 ( P  = .30). There was no significant change in post-deployment forced vital capacity (% predicted), from 93.8 ± 12.4 to 94.9 ± 12.1 ( P  = .42). The absolute change in forced expiratory volume at 1 second (L) after bronchodilator administration was decreased from pre-deployment to post-deployment (+0.31 ± 0.26 to +0.16 ± 0.23; P  = .02). Conclusions: There was no significant post-deployment change in spirometry in this military population with asthma deployed to southwest Asia. These findings suggest that deployment itself is not associated with any short-term deleterious effect on post-deployment spirometric measures of lung function in many military personnel with asthma.